Retrieval of Multiple Glass Shards from Periorbital Region: Challenges and Considerations - M. S Vidya; R Rakhi; A Roshni; Tom Thomas (Journal of Primary Care Dentistry and Oral Health)
Foreign entities implanted deep in facial tissues provide difficulty for maxillofacial surgeons as they are in close proximity to the vital structures, especially in the periorbital region. Foreign bodies embedded within the facial layers are typically identified through radiographs or may present later with swelling, pain, or pus discharge. Trauma to the craniofacial region, particularly as a result of road traffic accidents, is a major contributor to foreign body impaction. Despite this, many cases remain unrecognized. Here, we report a case where multiple fragmented glass pieces were retrieved from the maxillofacial region of a 45-year-old male through existing lacerations.